Civil liability in Labor contingencies - Arévalo Vela, Javier (2020)
This article studies the legislation, legal doctrine and jurisprudence referring to the civil liability of the employer in the labor contingencies, namely work accidents and occupational diseases. Thus, some basic concepts on the subject will be reviewed, and the nature of this legal institute will be analyzed, that has always been complex, since we have not yet found consensus or uniformity in the norm or in the authors.